Case Report: “Area of Focus” Atypical Trichinellosis and Fascioliasis Coinfection - Wang, Meng; Liu, Wei; Xiong, Ziman; Li, Zhen; Li, Jiansha; Xu, Xin; Zhang, Meng; Xing, Mingyou; Ning, Qin; Wu, Di; Qi, Junying (Frontiers in Medicine, 2022)
Parasitic co-infection is commonly observed in natural populations, yet rare in the laboratory. Multiparasitism can have negative effects on the host, ranging from the atypical manifestations to increased mortality, consequently, it may be misdiagnosed and treated with unsuitable anthelmintic medicines. Therefore, reliable diagnosis is critical for appropriate treatment of parasitic co-infection. Herein, we report a case of a 31-year-old woman with persistent eosinophilia and hypoechoic liver lesion on ultrasound. The microscopic examination of multiple stool specimens did not find any pathogens. The patient had serum specific anti-Trichinella IgG antibody by Dot enzyme-linked immunosorbent assay (Dot-ELISA). After treatment with albendazole, contrast-enhanced magnetic resonance imaging (MRI) revealed more lesions in the liver. Subsequently, liver biopsy was performed in this patient and Fasciola hepatica was identified using metagenomic next-generation sequencing (mNGS) as well as polymerase chain reaction. After treatment with triclabendazole, which is the only anthelmintic drug specifically available against this fluke, her eosinophil count returned normal, and the liver lesions were significantly regressed. This case highlights the diagnostic challenge posed by parasitic co-infection, which merits more in-depth evaluation to confirm the diagnosis.